СТАН ПРОБЛЕМ САМОКОНТРОЛЮ НАВЧАЛЬНОЇ ДІЯЛЬНОСТІ СТУДЕНТІВ У НАУКОВО-ПЕДАГОГІЧНІЙ ЛІТЕРАТУРІ (Педагогіка вищої та середньої школи, 2009)
In the article was considered theme of pedagogical control and self control of students of higher educational establishments with description of different constituents in the process of forming of awareness students them educational activity.